The effects of single session intervention on perceived control : a pilot study testing growth mindset amongst Malaysian adolescents - Fata, Fatin Nurafiqah Abdul (2021)
Adolescence is the transition period from being a child to being an adult. This is the period where they start fostering their psychological, emotional and physical growth. Individuals who believe that their abilities and skills can be improved through effort are said to adopt growth mindset. The present study aims to explore the effects of growth mindset intervention on levels of perceived control amongst adolescents. A within-subjects design was employed for the current study to investigate the effectiveness of a single session intervention (SSI) targeting growth mindset on levels of perceived control. Perceived control was measured using Primary Control Scale for Children (PCSC) and Secondary Control Scale for Children (SCSC) which measure the individual’s perception of control related to their external environment (primary perceived control) and perception of control directed at internal processes (secondary perceived control). Participants were recruited from local secondary school and undergo a 2-hour session delivered online, individually. The result indicated that adolescents benefitted from the brief, single session intervention as measured by their improved levels of perceived control. Adolescents reported having greater sense of control over their environment related to social situations and adjusting their internal processes to fit the external environment. The findings of the present pilot study raise the possibility of utilizing growth mindset as a therapeutic content to increase levels of perceived control in adolescents.